ANALYSIS OF STIMULATION AUDITORY SINCE THE DEVELOPMENT OF LANGUAGE IN CHILDREN AGES 12-24 MONTHS IN 19 TH AND 20 TH NEIGHBORHOOD ASSOCIATION, TAWANGSARI BARAT VILLAGE, SIDOARJO, EAST JAVA PROVINCE, INDONESIA - Firdaus Firda Firdaus; Erin Andini (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Speech delay is a problem that occurs in society commonly found in children. One of the factors affecting language development is the early sensory perception stimulation. Objectives: This study was purposed to analyze the correlation between early sensory perception stimulation and language development in children aged 12-24 months. Methods: This observational study was conducted using a cross-sectional approach. It involved 34 parents and their children aged 12-24 months as the population, in which 32 parents and their children were taken as the samples using simple random sampling technique. The independent variable was the early sensory perception stimulation, whereas the dependent variable was language development. The instruments used in this study were questionnaire and observation sheets. Furthermore, the collected data were analyzed using Spearman's rank correlation test with the significance level of α = 0.05. Results: The results of this study showed that nearly all of the respondents (89.5%) provided their children with the early sensory perception stimulation sufficiently. Consequently, most of the children (62.5%) experienced language development sufficiently. Moreover, the correlation test using Spearman's rank test showed that Sig. = 0.000 (p < 0.05) illustrating that p <α so that Ho was rejected. This result showed that there was a correlation between early sensory perception stimulation and language development in children aged 12-24 months. Conclusion: The early sensory perception stimulation which is given well to children will result in optimal language development. Hence, the health workers, especially the nurses, are expected to provide the family with a counseling program about the importance of giving the early sensory perception stimulation to children to optimize their language development. Key words: Early sensory perception stimulation, language development.